2017
DOI: 10.1371/journal.pone.0177010
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach to study the perception of animacy in dogs

Abstract: Humans tend to perceive inanimate objects as animate based on simple motion cues. So far this perceptual bias has been studied mostly in humans by utilizing two-dimensional video and interactive displays. Considering its importance for survival, the perception of animacy is probably also widespread among animals, however two-dimensional displays are not necessarily the best approach to study the phenomenon in non-human species. Here we applied a novel method to study whether dogs recognize a dependent (chasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 28 publications
(88 reference statements)
2
24
1
Order By: Relevance
“…On the other hand, there are several reports on primitive agents like remote control cars eliciting (evoking) dog's perception of interactivity or sociality toward the agent by acting in helpful and complex ways. Some researchers propose the importance of the agent's behavior to evoke dogs' perception of animacy or interactivity toward the agent [1]. In addition, the results in our exploratory experiment casted a new possibility of effective utilizing way of a physical agent with realistic embodiment evoking dog's perception as a "hook" in the first contact to some extent.…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, there are several reports on primitive agents like remote control cars eliciting (evoking) dog's perception of interactivity or sociality toward the agent by acting in helpful and complex ways. Some researchers propose the importance of the agent's behavior to evoke dogs' perception of animacy or interactivity toward the agent [1]. In addition, the results in our exploratory experiment casted a new possibility of effective utilizing way of a physical agent with realistic embodiment evoking dog's perception as a "hook" in the first contact to some extent.…”
Section: Discussionmentioning
confidence: 67%
“…In previous studies, we found that dogs, similarly to humans, perceive inanimate objects as animate based simply on their motion 8 , 9 , 20 , but species differences were also detected 9 . In two studies, we displayed to dogs simultaneously a chasing and independent motion side-by-side on a screen using geometric figures.…”
Section: Introductionmentioning
confidence: 75%
“…In another study, dogs interacted more often with objects that displayed a dependent movement pattern (resembling a chasing event) than with independently moving objects 17 . In a related looking time study, dogs lost interest sooner in geometric shapes with a dependent (chasing-like) movement pattern than in shapes with an independent movement pattern 18 .…”
Section: Introductionmentioning
confidence: 95%
“…Ishikawa and colleagues 16 only found increased looking times for a human point-light walker in frontal view but not in lateral view compared to inverted control stimuli. Eatherington and colleagues 15 In another study, dogs interacted more often with objects that displayed a dependent movement pattern (resembling a chasing event) than with independently moving objects 17 . In a related looking time study, dogs lost interest sooner in geometric shapes with a dependent (chasing-like) movement pattern than in shapes with an independent movement pattern 18 .…”
mentioning
confidence: 99%